İLK DÖNEM İSLÂM MANTIKÇILARININ MODAÜTEYE YAKLAŞIMI - İbrahim Çapak (Felsefe Dünyası)
This study explores the modal propositions and modal syllogisms of Muslim logicians such as Farabi, Ibn Sina, Ghazali, Abu Salt al-Dani and Ibn Tumlus. Although they all discuss the modal propositions, only Ibn Sina and Abu Salt al-Dani consider modal syllogisms important and examines all kinds of them in details. The study begins with the survey of all types of modal propositions, which can be classified in four main categories: absolute, possible, necessary, impossible. Then it gives early Muslim logicians' definition of absolute, possible, necessary and impossible propositions.